Depression and anxiety symptoms in male veterans and non‐veterans: the Health and Retirement Study. (22nd August 2014) - Gould, Christine E.; Rideaux, Tiffany; Spira, Adam P.; Beaudreau, Sherry A.
<x xml:space="preserve">Abstract</x> Objectives We examined whether veteran status was associated with elevated depression and anxiety symptoms in men aged 50 and older after adjusting for sociodemographic factors. Methods Participants were 6577 men aged 50 years and older who completed the 2006 wave of the Health and Retirement Study (HRS). Forty‐nine percent of participants were veterans. A randomly selected subset of participants completed the HRS Psychosocial Questionnaire (N = 2957), which contained the anxiety items. Elevated depression and anxiety symptoms were determined based on brief versions of Center for Epidemiologic Studies—Depression Scale (CES‐D total score ≥ 4) and Beck Anxiety Inventory (BAI total score ≥ 12). Results Elevated depression and anxiety symptoms were found in 11.0 and 9.9% of veterans, respectively, compared with 12.8 and 12.3% of non‐veterans. Veteran status was not associated with increased odds of anxiety or depression symptoms in the multivariable‐adjusted logistic regression analyses. Additional analyses indicated that Vietnam War veterans were more than twice as likely as World War II or Korean War veterans to have elevated depression symptoms (OR = 2.15, 95% CI: 1.54–3.00) or anxiety symptoms (OR = 2.12, 95% CI: 1.28–3.51). Conclusions In a community‐based sample of men aged 50 and older, veteran status was not associated with the presence of elevated depression and anxiety symptoms. Rather, these symptoms were associated with age, ethnicity, education, and medical conditions. Among veterans, cohort effects accounted for differences in psychiatric symptoms. Including younger cohorts from the Global War on Terror may yield different results in future studies. Copyright © 2014 John Wiley & Sons, Ltd.